Tax Morale in Asian Countries - Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2004)
This paper analyses tax morale in several Asian countries. The descriptive analysis indicates that tax morale is very low in the Philippines and relatively high in Japan, China, and Bangladesh. In general Asia has a higher tax morale than OECD countries, which might indicate cultural differences. The paper also analyses tax morale as a dependent variable and thus gives answers to what shapes tax morale. Pooling the Asian countries we find, e.g., that trust in the government and the legal system have a positive effect on tax morale. These results remain robust for India and Japan in a time series analysis.
Keywords: H26; K42; 330; tax morale; tax evasion; shadow economy